THEORETICAL ISSUES OF LINGUOPOETICS (CAHIERS MAGELLANES-NS, 2024)
It has long been known that issues related to the emergence of linguopoetics have attracted the attention of many researchers and caused debates and discussions. Lingvopoetics is not an emerging field today. The sciences within the concept represented by this term have long been studied as part of the philological field, and this field has been studied as part of social sciences, in particular, as part of philosophy.This article deals with issues related to the emergence of linguopoetics. The relationship between linguistics and poetics is shown.